Breast cancer awareness in reproductive women in the low- and middle-income countries: a scoping review - Nugraha Gautama Made Satya; Pimolkatekul Saranya; Nhat Thanh Nguyen Ngoc (Sciendo, 2024)
This study aimed to assess breast cancer (BC) awareness among reproductive women in low- and middle-income countries (LMICs), identify influencing factors, and propose feasible interventions or programs.